2020
DOI: 10.21203/rs.3.rs-125332/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dickkopf-1 Promotes Angiogenesis by Upregulating VEGF Receptor 2-mediated mTOR/p70S6K Signaling in Hepatocellular Carcinoma

Abstract: Background: The expression of Dickkopf-1 (DKK1), a negative regulator of the Wnt/β-catenin signaling pathway, is upregulated in hepatocellular carcinoma (HCC). Here, we investigated the tumorigenic and angiogenic potential of DKK1 in HCC.Methods: Stable cell lines were established using the clustered regularly interspaced short palindromic repeats (CRISPR)-associated nuclease 9 (CRISPR/Cas9)-based DKK1 knock-out system in Hep3B cells and the tetracycline-based DKK1 inducible system in Huh7 cells. Multicellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Among these genes, we noted that Dkk1 is an osteocyte-derived molecule, which was reportedly an inhibitor of Wnt signaling and an angiogenesis activator. [31][32][33] Because Ckap4 (a Dkk1 receptor) 34,35 and Plvap (plasmalemma vesicle-associated protein, an angiogenetic factor) 36 expressions were also elevated, we postulated that osteocyte-derived molecules, such as Dkk1, affected vascular endothelial cells to induce angiogenesis. This reaction potentially enables invasion into the cortical bone with osteoclasts in the PTH group.…”
Section: Discussionmentioning
confidence: 99%
“…Among these genes, we noted that Dkk1 is an osteocyte-derived molecule, which was reportedly an inhibitor of Wnt signaling and an angiogenesis activator. [31][32][33] Because Ckap4 (a Dkk1 receptor) 34,35 and Plvap (plasmalemma vesicle-associated protein, an angiogenetic factor) 36 expressions were also elevated, we postulated that osteocyte-derived molecules, such as Dkk1, affected vascular endothelial cells to induce angiogenesis. This reaction potentially enables invasion into the cortical bone with osteoclasts in the PTH group.…”
Section: Discussionmentioning
confidence: 99%
“…However, by altering the tumour microenvironment and causing inflammation, DKK1 seems to promote tumour invasion and migration via TGF-β1 [87]. Additionally, as recently shown, DKK1 stimulates HCC angiogenesis and tumorigenesis via VEGFR2mediated mTOR/p70S6K signalling [88].…”
Section: Opnmentioning
confidence: 92%
“…[76][77][78] Numerous studies have demonstrated a positive correlation between mTOR signaling and angiogenesis in ischemic brain injury. 79,80 It has been reported that COMP-Ang1 induced prominent angiogenesis through an AKT/mTOR interaction, leading to enhanced migration of human cord blood-derived endothelial progenitor cells, tube formation, and vascular morphogenesis. Besides, the combined treatments of endothelial progenitor cells and COMP-Ang1 effectively mitigated ischemic brain injury by increasing angiogenesis.…”
Section: Activation Of Mtor Promotes Angiogenesis After Cerebral Isch...mentioning
confidence: 99%